Whole Gene Capture Analysis of 15 CRC Susceptibility Genes in Suspected Lynch Syndrome Patients. - Anne M L Jansen; Marije A Geilenkirchen; Tom van Wezel; Shantie C Jagmohan-Changur; Dina Ruano; Heleen M van der Klift; Brendy E W M van den Akker; Jeroen F J Laros; Michiel van Galen; Anja Wagner; Tom G W Letteboer; Encarna B Gómez-García; et al. (PLoS ONE, 2016)
BACKGROUND AND AIMS:Lynch Syndrome (LS) is caused by pathogenic germline variants in one of the mismatch repair (MMR) genes. However, up to 60% of MMR-deficient colorectal cancer cases are categorized as suspected Lynch Syndrome (sLS) because no pathogenic MMR germline variant can be identified, which leads to difficulties in clinical management. We therefore analyzed the genomic regions of 15 CRC susceptibility genes in leukocyte DNA of 34 unrelated sLS patients and 11 patients with MLH1 hypermethylated tumors with a clear family history. METHODS:Using targeted next-generation sequencing, we analyzed the entire non-repetitive genomic sequence, including intronic and regulatory sequences, of 15 CRC susceptibility genes. In addition, tumor DNA from 28 sLS patients was analyzed for somatic MMR variants. RESULTS:Of 1979 germline variants found in the leukocyte DNA of 34 sLS patients, one was a pathogenic variant (MLH1 c.1667+1delG). Leukocyte DNA of 11 patients with MLH1 hypermethylated tumors was negative for pathogenic germline variants in the tested CRC susceptibility genes and for germline MLH1 hypermethylation. Somatic DNA analysis of 28 sLS tumors identified eight (29%) cases with two pathogenic somatic variants, one with a VUS predicted to pathogenic and LOH, and nine cases (32%) with one pathogenic somatic variant (n = 8) or one VUS predicted to be pathogenic (n = 1). CONCLUSIONS:This is the first study in sLS patients to include the entire genomic sequence of CRC susceptibility genes. An underlying somatic or germline MMR gene defect was identified in ten of 34 sLS patients (29%). In the remaining sLS patients, the underlying genetic defect explaining the MMRdeficiency in their tumors might be found outside the genomic regions harboring the MMR and other known CRC susceptibility genes.